2007
DOI: 10.1002/j.2161-1920.2007.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Who is and who is not willing to use online employer‐provided retirement investment advice

Abstract: This study used classification tree analysis to examine who is and who is not willing to use online employer‐provided retirement investment advice. Using data from the Retirement Confidence Survey (Employee Benefit Research Institute, 2004), the study focused on who was more likely to use online retirement investment advice when it was available from their employer. Results indicated that those who were younger, those who participated in a defined contribution retirement plan, and those who made joint (with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…They found that health condition was in tandem with the desire and confidence to use the Internet. Similar findings were obtained in earlier studies where financial status was seen as a relevant factor in the older adults' selfconfidence in Internet use (Czaja et al, 2006;Joo et al, 2007).…”
Section: Factors Impacting Older Adults' Self-efficacy In Computer Usesupporting
confidence: 90%
See 1 more Smart Citation
“…They found that health condition was in tandem with the desire and confidence to use the Internet. Similar findings were obtained in earlier studies where financial status was seen as a relevant factor in the older adults' selfconfidence in Internet use (Czaja et al, 2006;Joo et al, 2007).…”
Section: Factors Impacting Older Adults' Self-efficacy In Computer Usesupporting
confidence: 90%
“…Evidence from empirical research indicates the individual's overall life satisfaction is related to health, income, financial status, and job satisfaction (Joo et al, 2007;O'Conner, 2013). Cresci and Novak (2012) examined urban elders' collective perceptions on health condition/financial status and overall life satisfaction.…”
Section: Overall Life Satisfaction As a Mediatormentioning
confidence: 99%
“…They found that health condition was in tandem with the desire and interest to know what to expect as one grows older. Individuals' financial status is also increasingly perceived to be connected with Internet use (Joo, Grable, & Choe, 2007;O'Connor, 2013). Tien and Tsai (2013) found that older adults consider the Internet to be one of major resources for financial consultation and management.…”
Section: Examined Urban Elders' Older Adults' Perceptions Of Internetmentioning
confidence: 98%